Mixed Cation FAxPEA1–xPbI3 with Enhanced Phase and Ambient Stability toward High‐Performance Perovskite Solar Cells. Issue 1 (26th September 2016) - Li, Nan; Zhu, Zonglong; Chueh, Chu‐Chen; Liu, Hongbin; Peng, Bo; Petrone, Alessio; Li, Xiaosong; Wang, Liduo; Jen, Alex K.‐Y.
Abstract : In this work, different from the commonly explored strategy of incorporating a smaller cation, MA + and Cs + into FAPbI3 lattice to improve efficiency and stability, it is revealed that the introduction of phenylethylammonium iodide (PEAI) into FAPbI3 perovksite to form mixed cation FAx PEA1–x PbI3 can effectively enhance both phase and ambient stability of FAPbI3 as well as the resulting performance of the derived devices. From our experimental and theoretical calculation results, it is proposed that the larger PEA cation is capable of assembling on both the lattice surface and grain boundaries to form quais‐3D perovskite structures. The surrounding of PEA + ions at the crystal grain boundaries not only can serve as molecular locks to tighten FAPbI3 domains but also passivate the surface defects to improve both phase and moisture stablity. Consequently, a high‐performance (PCE:17.7%) and ambient stable FAPbI3 solar cell could be developed. Abstract : The introduction of a bulkier phenylethylammonium cation into FAPbI3 is revealed to effectively enhance both phase and ambient stability of FAPbI3 . The larger hydrophobic cation is proposed to assemble on lattice surface and grain boundaries to form quasi‐3D perovskite structures, which tightens FAPbI3 domains and passivates surface defects, leading to a efficient and stable FAPbI3 based solar cell.